Roles of exosomes in immune regulation of osteoarthritis and their applications in inflammation repair - Lan, Shuquan; Zhang, Chao (Frontiers in Immunology, 2025)
Osteoarthritis (OA) is a chronic, degenerative joint disease characterized by progressive cartilage degradation and inflammation. Exosomes, small vesicles released by various cell types, play a crucial role in mediating immune responses and inflammation. In OA, exosomes from antigen-presenting cells (APCs) promote synovial inflammation through antigen presentation and cytokine signaling, while those from mesenchymal stem cells (MSCs) modulate inflammation by reprogramming macrophages. Exosomal cargo has shown potential in controlling inflammatory pathways and protecting cartilage from degradation. MSC-derived exosomes have demonstrated therapeutic promise in reducing OA-related inflammation and promoting cartilage regeneration. Despite several reports have outlined the role of exosomes or immune modulation in OA individually, comprehensive reviews integrating their roles in both immune regulation and inflammation repair in OA are still lacking. This knowledge gap hinders the translational application of exosome-based interventions in clinical settings. This review aims to summarize the immunoregulatory roles of exosomes in OA, emphasizing their impact on inflammation and immune responses, and discusses their therapeutic potential in OA treatment. By elucidating the roles of exosomes, the findings of this review could facilitate the development of novel, minimally invasive strategies for improving OA treatment and enhancing inflammation repair.